2012
DOI: 10.1007/s00266-012-9899-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Melasma With Oral Administration of Tranexamic Acid

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors at www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
127
4
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(146 citation statements)
references
References 29 publications
7
127
4
8
Order By: Relevance
“…Wu U et al reported in their study found out significant improvement in the physicians rating scale following oral TXA 250 mg twice daily administration for a period of 6 months for 74 patients, in which 54% had good outcome, 31.1% had fair outcome and 4.1% poor outcome in their study. (9) Neerja puri et al in their study compared oral TXA Vs triple combination regimen for the treatment of melasma, where they found 64% of MASI score improved in oral TXA group, where as only 56% in triple combination therapy. (10) Cristina C et al evaluated the efficacy of the topical with TXA with micro needling in the treatment of melasma.…”
Section: Discussionmentioning
confidence: 99%
“…Wu U et al reported in their study found out significant improvement in the physicians rating scale following oral TXA 250 mg twice daily administration for a period of 6 months for 74 patients, in which 54% had good outcome, 31.1% had fair outcome and 4.1% poor outcome in their study. (9) Neerja puri et al in their study compared oral TXA Vs triple combination regimen for the treatment of melasma, where they found 64% of MASI score improved in oral TXA group, where as only 56% in triple combination therapy. (10) Cristina C et al evaluated the efficacy of the topical with TXA with micro needling in the treatment of melasma.…”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid has also been reported to have biochemical/physiological behavior that needs further investigation. When tranexamic acid was applied topically to the entire facial area, it lightened areas of melasma, but not other pigmented areas such as senile lentigo or freckles [1]. Also, in two other studies in humans, in one study it increased levels of occludin, the tight junction protein important in epithelial barrier formation [11], but in a second study, it failed to increase levels of collagen IV, the biomarker for basement membrane integrity, to those seen in normal skin [4].…”
Section: Discussionmentioning
confidence: 99%
“…It was first used as a hemostatic agent and is now, at lower doses, used as a skin whitener and as an ingredient in some cosmetic creams. When used as an oral treatment, 500 mg/day for 6 months was reported to be effective in the treatment of melasma [1], and 750 mg/day for 8 weeks was reported to improve the effectiveness of laser treatment of melasma [2]. Eight weeks of topical treatment with or without the addition of oral treatment has also been reported to be effective as a treatment of melasma [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tranexemic acid by way of its antiplasmin activity depletes the keratinocyte pool of arachidonic acid involved in ultraviolet (UV) induced melanogenesis. [13][14][15][16][17] It has been used at a low dose of 250 mg twice a day for at least 3 months for the treatment of melasma and found to be effective. [15] But, it is not safe to use it for a long duration in view of its anti-hemorrhagic property resulting in side effects like venous thromboembolism, myocardial infarction, cerebrovascular accidents and pulmonary embolism.…”
Section: Tranexemic Acidmentioning
confidence: 99%